Structured FORTRAN 77 for engineers and scientists - Etter, Delores M. (Benjamin/Cummings Pub. Co., 1990)
Contents: An introduction to FORTRAN 77 and problem solving; Arithmetic computations; Control structures; Array procesing; Additional data types; Additional file handling...